Hypereosinophilic syndrome: an indolent rash with a serious cardiac complication. (1st March 2016) - Merika, E. E.; Lefroy, D.; Milojkovic, D.; Wakelin, S. H.
Summary: Idiopathic hypereosinophilic syndrome (HES) is a rare disorder, characterized by prominent blood or tissue eosinophilia with ensuing tissue damage, which is diagnosed after exclusion of underlying diseases known to cause HES. Sustained eosinophilia is associated with cardiac disease, including endomyocardial thrombosis and fibrosis, leading to restrictive cardiomyopathy, valvular dysfunction and increased thrombotic tendency. Aneurysmal coronary artery disease (CAD) occurring in the absence of stenotic atherosclerotic plaques is extremely rare. We present a case of idiopathic HES in a 30‐year‐old woman with asymptomatic multianeurysmal CAD and a sinus of Valsalva aneurysm, and discuss a brief review of the literature and management strategies.